Data underlying the publication: Impacts of direct and indirect pathways of convected water masses on the overturning dynamics of the Labrador Sea - Georgiou, Sotiria (4TU.ResearchData, 2020)
MOM mean fields and Lagrangian particle data set used for publication in the Journal of Geophysical Research: Oceans